FINAL NEO-CARBON ENERGY COUNTDOWN : Ready for Renewables - Heinonen, Sirkka; Honkapuro, Samuli; Karjalainen, Joni; Koljonen, Tiina; Ruotsalainen, Juho; Similä, Lassi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
Renewables-based Neo-Carbon Vision of the world in 2050 portrays an electrified, resilient and secure society with empowered, prosumeristic citizens who upload their surplus energy into smart grids as well as download energy when needed. The following overview on key insights of the Neo-Carbon Energy project on energy futures helps to frame the academic and societal discourse in the years to come. Four scenarios assume a social perspective to open up very different avenues as transformative manifestations of this vision. The vision shows the pre-ferred goal – a renewables-based society – while the scenarios outline alternative expressions and pathways towards the desired vision. Finally, the actors that can make this change happen have to be identified and supported, especially in policy-making, and the role of energy markets re-thought.